Synergy of tensile strength-ductility in IN718/CoCrFeMnNi/IN718 multi-material processed by powder high-pressure torsion and annealing. (1st March 2023) - Gu, Gang Hee; Heo, Yoon-Uk; Kwon, Hyeonseok; Ahn, Soung Yeoul; Son, Sujung; Asghari-Rad, Peyman; Kim, Hyoung Seop
Abstract: Materials manufactured through conventional powder metallurgy (PM) techniques generally exhibit inferior tensile properties due to structural defects. Nevertheless, a recently proposed cold-consolidation technique using powder high-pressure torsion represents well-manufactured structures with ultra-high tensile properties in the absence of cracks or pores. This novel PM-based technique is utilized in the present investigation to fabricate a multi-material Inconel 718/CoCrFeMnNi/Inconel 718 layered structure. By a combination of uttermost high densification, ultra-fine-grained microstructure, and hetero-deformation induced strengthening effect, the present cold-consolidated multi-material exhibits tensile properties with yield strength of 1255.4 MPa, uniform elongation of 13.7%, and total elongation of 25.0%, overcoming monolithic Inconel 718 and CoCrFeMnNi systems. These findings shed light on the capability of the cold-consolidation technique to manufacture multi-layered and gradient multi-functional structures with excellent mechanical response under tensile stress. Graphical abstract: Image, graphical abstract